2022
DOI: 10.1161/circep.122.011120
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Field Ablation of the Porcine Ventricle Using a Focal Lattice-Tip Catheter

Abstract: Background: Our understanding of catheter-based pulsed field ablation (PFA) of the ventricular myocardium is limited. We conducted a series of exploratory evaluations of ventricular PFA in swine ventricles. Methods: A focal lattice-tip catheter was used to deliver proprietary biphasic monopolar PFA applications to swine ventricles under general anesthesia, with guidance from electroanatomical mapping, fluoroscopy, and intracardiac echocardiography. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Langendorff and whole-animal studies have been completed in swine [ 52 , 53 , 54 , 55 , 56 , 57 ], canine [ 58 ], ovine [ 59 ], and even rabbit [ 60 ] models using various PFA catheter types and methodologies. Consensus findings include the creation of transmural lesions via concentrated apoptosis with no evidence of thermal-based tissue damage.…”
Section: Pulsed-field Ablation For Arrhythmogenic Substrate Suppressionmentioning
confidence: 99%
“…Langendorff and whole-animal studies have been completed in swine [ 52 , 53 , 54 , 55 , 56 , 57 ], canine [ 58 ], ovine [ 59 ], and even rabbit [ 60 ] models using various PFA catheter types and methodologies. Consensus findings include the creation of transmural lesions via concentrated apoptosis with no evidence of thermal-based tissue damage.…”
Section: Pulsed-field Ablation For Arrhythmogenic Substrate Suppressionmentioning
confidence: 99%
“…[6] Major medical companies are already ahead of the curve, acquiring or developing their own PFA catheters (such as FaraPulse from Boston Scientific Corporation, PulseSelect from Medtronic, and Varipulse from Johnson and Johnson) and putting them into clinical trials to collect first-line data and seek food and drug administration approval. [11][12][13][14] While still in the preclinical stage, several studies have demonstrated the excellent efficiency, safety, and durability of PFA. [8,12,[15][16][17] However, to date, these electrodes featuring large dimensions (25-35 mm) and insufficient ablation precision (at least a dozen millimeters) have often led to "overkill" during myocardial conduction block.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Major medical companies are already ahead of the curve, acquiring or developing their own PFA catheters (such as FaraPulse from Boston Scientific Corporation, PulseSelect from Medtronic, and Varipulse from Johnson and Johnson) and putting them into clinical trials to collect first‐line data and seek food and drug administration approval. [ 11–14 ]…”
Section: Introductionmentioning
confidence: 99%
“…The experimental data comparing PFA lesions on healthy myocardium and scar (healed infarction) tend to be rather scarce and are limited to pre-clinical models [3−5]. The preliminary results suggest that a superficial scar does not significantly impair PFA and creates lesion depths in healthy myocardium similar to adjacent healed endocardial scars (4.8 and 5.6 mm, respectively) [ 3 ]. Although the preliminary experimental data suggests that PFA may be superior to RFA in terms of being able to ablate viable myocardium separated from the catheter by collagen and fat [ 5 ], there is as yet no formal analysis based on physical laws that describes the process by which intramyocardial fat can affect the electric field distribution and alter the size of the PFA-induced lesion.…”
Section: Introductionmentioning
confidence: 99%